Research in the Social Scientific Study of Religion, Volume 31 : A Diversity of Paradigms - Hood, Ralph W.; Cheruvallil-Contractor, Sariya (Research in the Social Scientific Study of Religion, 2021)
Research in the Social Scientific Study of Religion, Volume 31: A Diversity of Paradigms showcases two approaches to the socio-scientific study of religion. It includes a special section within which authors draw on data collected about congregational life in the Australian National Church Life Surveys (from 1991 to present) These studies give voice to minority groups and children. While findings include the strengths of ethnic diversity and the positive experiences of young churchgoers, they also highlight that full inclusion in local church life is far from being realized. A second section explores the application of feminist approaches within the sociology of religion. In their struggle for equality for women, feminist scholars developed methodologies to challenge the marginality of any 'othered' group. This section showcases how use of these methods challenges hierarchies within knowledge.